Classification of contaminants in diesel engine oils - S. V. Pashukevich (Вестник СибАДИ)
Introduction. The deterioration of engine oil in an internal combustion engine (ICE) is directly related to the ingress of various pollutants into the crankcase. Depending on the type of contamination, the type of sediment on engine part surfaces varies. It should be noted that the functioning of the motor oil is extremely affected by the oxidation process, and organic acids produced during the process contribute to corrosion of ICE parts. Water, diesel, cooling fluid, soot particles, asphaltenes, etc. also cause irreparable damage.Materials and methods. This paper presents the results of an extensive literature review aimed at studying the main types of motor oil pollutants. Classifications are given for the aggregate state of pollutants, as well as for possible ways of their penetration into the lubricant. Liquid pollutants are the most narrowly considered in this article. To demonstrate the negative effect of contaminants entering the engine oil, photographs of internal combustion engine parts with sediments on the surfaces of the internal combustion engine components are presented.Results. The classification of the main pollutants of motor oils is given; the consequences arising from the ingress of foreign compounds into the lubricant in question are indicated.Conclusion. The effect of contaminants on the parts of the internal combustion engine and the lubricant has been established. On the basis of the classification, it is possible to judge the causes of entry and the possible consequences of the impact of contamination on the operation of the engine.